First Aid Application Development Android Smartphone - Imamul Huda (Institute of Computer Science (IOCS), 2021)
Rapid technological advances have turned mobile mobile devices into smartphones that have various applications in them. So that the smartphone device becomes the main need for its users. Several new breakthroughs can be present on smartphones such as applications around health. Where accidents can happen to anyone, anywhere and anytime. First aid measures are very important to do to reduce the impact of accidents. So the researchers developed an Accident First Aid (P3K) application on the Android platform with version 2.2 Froyo. The first aid application has a main feature that contains tutorials on first aid measures in an accident, as well as several additional features in the form of drug information, information on the location of the nearest hospital and pharmacy, types of rescue techniques, and emergency number calls. By using the Rapid Application Development system development methodology which consists of three phases, namely planning, design and implementation of the workshop, this application is made using the Android SDK Framework, Java Programming Language, googlemaps as a spatial data service and system testing has been carried out using the Black Box testing method. . This application, which has a file memory of 3.5Mb, can help smartphone users to recognize, learn and understand various first aid measures and become an application that can help victims when an accident occurs. googlemaps as a spatial data service and system testing has been carried out using the Black Box testing method. This application, which has a file memory of 3.5Mb, can help smartphone users to recognize, learn and understand various first aid measures and become an application that can help victims when an accident occurs. googlemaps as a spatial data service and system testing has been carried out using the Black Box testing method. This application, which has a file memory of 3.5Mb, can help smartphone users to recognize, learn and understand various first aid measures and become an application that can help victims when an accident occurs.